IMPLEMENTASI CUSTOMER RELATIONSHIP MANAGEMENT PADA SISTEM INFORMASI PEMESANAN CAKE AND DESSERT - Umar, Najirah; Rizkha, Andi Nur; Nasrullah, Nasrullah (Jurnal Teknoinfo, 2024)
This study aims to implement Customer Relationship Management (CRM) in the Cake and Dessert ordering information system. The research was conducted with a focus on the use of CRM to improve customer relationships, improve operational efficiency, and improve service quality in the context of businesses engaged in making and ordering cakes and desserts. There are several problems faced, such as the promotion process has not used a marketing strategy through the website, the reach of buyers is very limited, there is often a buildup of cakes and desserts which results in many expired cakes, there is no system that records order transactions, customer data. Research Design using UML, includes model use case diagrams, activity diagrams, sequence diagrams and class diagrams. The results showed that the implementation of CRM in the Cake and Dessert ordering information system provides a number of benefits, such as increased customer interaction, more effective customer data management, optimization of the order process, and increased customer satisfaction. This research provides important insights into CRM implementation in the cake and dessert ordering industry, and can be a reference for SMES who want to introduce or improve the use of CRM in their information systemsabstract is a brief summary of a paper to help readers quickly ascertain the purpose of the study and according to research needs.